Zionism and land tenure in mandate Palestine - Essaid, Aida Asim (Routledge studies on the Arab-Israeli conflict, 2014)
"A fundamental aspect of the conflict between Palestinians and Israelis is the territorial dispute which began long before the State of Israel was established. Analysing the land tenure system in Palestine under the administration of the British Mandate, this book questions whether, and to what extent, the land tenure system in Palestine facilitated Zionist land acquisition.The research uses benchmarks elaborated in the guidelines of the United Nations Human Settlements Programme as its analytical starting point, and looks at the formation and implementation of the land tenure system in Palestine. It goes on to place the penetration of Zionism into the land tenure system within the theoretical context of a colonial-settler framework, employing information from land registry records located at the Jordanian Department of Lands.Providing a political-historical analysis of the land tenure system from the end of Ottoman Rule until the end of the British Mandate, this book will be of interest to scholars and students of Middle Eastern History, Imperial and Colonial History, and Middle Eastern Politics"-